2007
DOI: 10.4049/jimmunol.178.8.4811
|View full text |Cite
|
Sign up to set email alerts
|

The A Subunit of Type IIb Enterotoxin (LT-IIb) Suppresses the Proinflammatory Potential of the B Subunit and Its Ability to Recruit and Interact with TLR2

Abstract: The type IIb heat-labile enterotoxin of Escherichia coli (LT-IIb) and its nontoxic pentameric B subunit (LT-IIb-B5) display different immunomodulatory activities, the mechanisms of which are poorly understood. We investigated mechanisms whereby the absence of the catalytically active A subunit from LT-IIb-B5 renders this molecule immunostimulatory through TLR2. LT-IIb-B5, but not LT-IIb, induced TLR2-mediated NF-κB activation and TNF-α production. These LT-IIb-B5 activities were antagonized by LT-IIb; however,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
70
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 35 publications
(70 citation statements)
references
References 49 publications
0
70
0
Order By: Relevance
“…Alignments revealed that the 27.31-kDa polypeptide of OS-1 was homologous to the A polypeptides of type II HLTs and to the A polypeptides of type I HLTs (Table 2). Amino acids Arg7, Asp9, His44, Ser61, Val97, Tyr104, Pro106, His107, Glu110, and Glu112, which are crucial for the ADP-ribosylating activity of CT and LT-I (35) and LT-IIb (19), were identified in the 27.31-kDa polypeptide, albeit shifted by two amino acid positions (Fig. 4).…”
Section: Methodsmentioning
confidence: 99%
“…Alignments revealed that the 27.31-kDa polypeptide of OS-1 was homologous to the A polypeptides of type II HLTs and to the A polypeptides of type I HLTs (Table 2). Amino acids Arg7, Asp9, His44, Ser61, Val97, Tyr104, Pro106, His107, Glu110, and Glu112, which are crucial for the ADP-ribosylating activity of CT and LT-I (35) and LT-IIb (19), were identified in the 27.31-kDa polypeptide, albeit shifted by two amino acid positions (Fig. 4).…”
Section: Methodsmentioning
confidence: 99%
“…However, upon Ab-mediated neutralization of IL-10, we did not observe significant reversal of the inhibitory effects (not shown). We then turned our attention to cAMP because inhibition of NF-B and TNF-␣ and concomitant augmentation of IL-10 are reminiscent of the immunomodulatory action of cAMP-inducing enterotoxins, as we previously observed (17).…”
Section: Pg-fimbriae Induce Cxcr4-mediated Activation Of Camp-dependentmentioning
confidence: 99%
“…Levels of cAMP in activated cell extracts were measured by using a cAMP enzyme immunoassay kit (Cayman Chemical) (17). Induction of PKA activity was determined by using lysates of activated cells and the ProFluor PKA assay (Promega).…”
Section: Cellular Activation Assaysmentioning
confidence: 99%
“…BspA binding to TLR2. TLR2 binding was measured as previously described (18). Briefly, 96-well microtiter wells were coated overnight at 4°C with 20 g/ml of purified recombinant mouse TLR2 (R&D Systems, Minneapolis, MN).…”
mentioning
confidence: 99%